A review on the role of miR-671 in human disorders - Ghafouri-Fard, Soudeh; Askari, Arian; Hussen, Bashdar Mahmud; Rasul, Mohammed Fatih; Hatamian, Sevak; Taheri, Mohammad; Kiani, Arda (Frontiers in Molecular Biosciences, 2022)
miR-671 is encoded by a gene on 7q36.1 and contributes to the pathogenesis of a variety of disorders, including diverse types of cancers, atherosclerosis, ischemic stroke, liver fibrosis, osteoarthritis, Parkinson’s disease, rheumatoid arthritis, acute myocardial infarction and Crohn's disease. In the context of cancer, different studies have revealed opposite roles for this miRNA. In brief, it has been shown to be down-regulated in pancreatic ductal carcinoma, ovarian cancer, gastric cancer, osteosarcoma, esophageal squamous cell carcinoma and myelodysplastic syndromes. Yet, miR-671 has been up-regulated in glioma, colorectal cancer, prostate cancer and hepatocellular carcinoma. Studies in breast, lung and renal cell carcinoma have reported inconsistent results. The current review aims at summarization of the role of miR-671 in these disorders focusing on its target mRNA in each context and dysregulated signaling pathways. We also provide a summary of the role of this miRNA as a prognostic factor in malignancies.